2007
DOI: 10.1021/jp066837j
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Dimethoxydimethylsilane:  Matrix Isolation Infrared and ab Initio Studies

Abstract: Conformations of dimethoxydimethylsilane (DMDMS) were studied using matrix isolation infrared spectroscopy, by trapping the silane in argon and nitrogen matrixes. The matrix was deposited using both an effusive and a supersonic jet source. The effusive source was maintained at two different temperatures, viz. 298 and 433 K, during deposition to alter the conformational population of the silane. The experimental results were supported by computations performed at both the HF and B3LYP levels, using 6-31++G** ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is therefore imperative to screen out conformers that are expected to have large energies, relative to the ground state conformer. On the basis of our earlier work on trimethyl phosphate (TMP), triethyl phosphate (TEP), , acetals/ketals, and silanes (all of which have a structural similarity with TBP), it has now become clear that a combination of hyperconjugative (the effect arises due to the delocalization interactions) and steric interactions decide the conformational preferences in these molecules. The study of trimethyl phosphite (TMPhite) which lacks a PO group, has highlighted the importance of the PO group in conformational preferences …”
Section: Introductionmentioning
confidence: 99%
“…It is therefore imperative to screen out conformers that are expected to have large energies, relative to the ground state conformer. On the basis of our earlier work on trimethyl phosphate (TMP), triethyl phosphate (TEP), , acetals/ketals, and silanes (all of which have a structural similarity with TBP), it has now become clear that a combination of hyperconjugative (the effect arises due to the delocalization interactions) and steric interactions decide the conformational preferences in these molecules. The study of trimethyl phosphite (TMPhite) which lacks a PO group, has highlighted the importance of the PO group in conformational preferences …”
Section: Introductionmentioning
confidence: 99%
“…The structure–property correlation assumes significance, as understanding at the molecular level in deriving the properties in bulk becomes indispensable. Earlier in our laboratory, a variety of systems, such as acetals–ketals, silanes, and carbonates, , were studied for conformations using matrix isolation infrared spectroscopy. These studies highlighted that the conformations of carbons attached to oxygens are driven through hyperconjugative charge transfer interaction and steric factor decides the conformations of rest of the carbons.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, imperative to find out the entire conformational picture of TAP through a simplified approach. On the basis of our earlier work on trimethyl phosphate (TMP), triethyl phosphate (TEP), , acetals/ketals, silanes, carbonates, , and phosphite, we concluded that a combination of hyperconjugative (arises due to the delocalization interactions) and steric interactions decides the conformational preferences in these molecules. It is interesting to probe the conformations of TAP as the knowledge on conformations would serve as a platform to understand its chemistry in the condensed phase.…”
Section: Introductionmentioning
confidence: 99%